Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems 2015
DOI: 10.1145/2702613.2732815
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Physical Activities in an Employer-Sponsored Health Program

Abstract: This work brings a perspective from an employersponsored health and wellness program called Global Corporate Challenge (GCC) to the 'quantified self' research. We present preliminary findings from a study with 17 university employees who participated in the GCC. We aimed to explore how participants derived meaningfulness from their self-tracking experiences. Our findings echo the growing body of work that advocates for conceptualizing activity tracking beyond the rationalistic, data-oriented perspectives and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Following Mukhopadhyay, Rajiv, and Srinivasan (1997), a technology's disruptiveness manifests in substantial changes of work processes. The introduction of physiolytics at the workplace, as demonstrated by exemplary prototypes in Table 1, exhibits features of disruptiveness due to the fact that it may significantly impact the design and execution of certain work activities (Cheng et al, 2013;Valero et al, 2016) and social structure among employees (Chung & Danis, 2016;Gorm & Shklovski, 2016;Vyas et al, 2015). Given that some of the presented applications scenarios entail severe organizational and cultural changes, considerable insecurities and unpredictable employee behaviour could result (Elie-Dit-Cosaque & Straub, 2011; Lapointe & Rivard, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Mukhopadhyay, Rajiv, and Srinivasan (1997), a technology's disruptiveness manifests in substantial changes of work processes. The introduction of physiolytics at the workplace, as demonstrated by exemplary prototypes in Table 1, exhibits features of disruptiveness due to the fact that it may significantly impact the design and execution of certain work activities (Cheng et al, 2013;Valero et al, 2016) and social structure among employees (Chung & Danis, 2016;Gorm & Shklovski, 2016;Vyas et al, 2015). Given that some of the presented applications scenarios entail severe organizational and cultural changes, considerable insecurities and unpredictable employee behaviour could result (Elie-Dit-Cosaque & Straub, 2011; Lapointe & Rivard, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, other scholars (Chung & Danis, 2016;Glance, Ooi, Berman, & Glance, 2016;Gorm, 2016;Vyas et al, 2015) have reported on employer-sponsored health programs that include physical activity tracking in order to generally reduce physical inactivity. Physiolytics solutions in these programs, apart from pedometers, additionally include user-centred applications for the definition of goals, the reporting of goal achievements, and for performance benchmarking.…”
Section: Application Scenarios Of Physiolytics At the Workplacementioning
confidence: 97%
See 1 more Smart Citation
“…These research findings have led employers to develop programs to promote walking for health among their employees [4] [16] [32]. In the short-term, these studies showed promising results, finding that social relationships in the organization affect employee inclination to participate [4] [16].…”
Section: Engagement With Fitness Trackingmentioning
confidence: 99%
“…First, it has favored the idea that health is not a private matter anymore [5]. Given that "chronic diseases generate billions of dollars in avoidable health expenditure every year" [6], companies and governments alike have used this argument for political reasoning and actions [7], paving the way for large-scale (digital) organizational and public health prevention and promotion programs [8][9][10] which have fostered the belief that much disease is caused by unhealthy life choices and that there is a moral obligation to exercise healthy behavior to reduce the financial burden on society [11]. In this sense, engaging in unhealthy behavior or even worse-having a chronic disease due to years of personal neglect and misdemeanor-imposes a moral dilemma and guilt on citizens, arising from failure or incompetence to fulfil the inherent social norms.…”
Section: Introductionmentioning
confidence: 99%